If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x = 2x + 13 Reorder the terms: 6x = 13 + 2x Solving 6x = 13 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 6x + -2x = 13 + 2x + -2x Combine like terms: 6x + -2x = 4x 4x = 13 + 2x + -2x Combine like terms: 2x + -2x = 0 4x = 13 + 0 4x = 13 Divide each side by '4'. x = 3.25 Simplifying x = 3.25
| 14-x+-m=3x+17 | | .30-p=250-p | | Y+7=-3(x-2) | | 6.4-3(m+1)=(-38) | | 9x+1=x+13 | | 5k+7=23 | | (x-3/2)-2=(x-8/3) | | -6-6x=-6(1+8x)+3x | | =7l-2[3(5l-m)-2(4l+m)] | | 2x+65=7x+128 | | 5x+8-4x=5+4 | | 1/4(b-3)=5/2 | | -3(2x-5)=180 | | x(.053)+x=196.64 | | -6-6x=-6(18x)+3x | | 6x-22=2x+22 | | 5xcubed=245 | | 2x-4-12=-4+3x+1 | | 2x+22=2x+22 | | -2x-6=-3x+10 | | 10x-5=7x+3 | | 4x=(x+99) | | 5a-2=2a-8 | | x+1.5+1.5=17 | | 10x+10=7x+13 | | (X+99)=4x | | 5e-1=3e+7 | | (2n/5)-(3/7)=13/35 | | 4t=5t+7 | | P=3x^2+30x+12 | | -16+6x=2(x-6) | | 4x=(75-x) |